(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The difficulties faced by social enterprises; similarities between social work practice and social entrepreneurship in terms of the types of work done, industries served, and results achieved. In a similar vein, it was thought that social entrepreneurs and social work practitioners share some traits, abilities, ambitions, and duties despite the fact that social entrepreneurs come from different demographic backgrounds. Social entrepreneurship, like any other industry, has its fair share of problems. While Hossain (2020) argues that, regardless of context, social entrepreneurs face the same overarching challenges, such as inadequate funding, difficulty scaling up, conflicting missions, and an inadequate business strategy, many other obstacles are context dependent. Consequently, it is crucial to learn about the problems and difficulties faced by Kerala’s social entrepreneurship sector.